Modeling of IGBT junction temperature based on load torque variation in induction motor - Ahmed Shihab Mayyahi; Riyadh Ghanem Omar (Institute of Advanced Engineering and Science, 2023)
In order to discuss the effectiveness of inverter performance, it is essential to concentrate on its losses. Thus, knowing the junction temperature (TJ) value of the inverter switches insulated-gate bipolar transistor (IGBTs) under different loading conditions allows determining their reliability and designing the right heat sink. The old methods to calculate the TJ are inaccurate, difficult to implement, and require mathematical analysis. So, in this work, a new approach was used to calculate the TJ in a simplified way, using the SIMSCAPE environment in the MATLAB simulation. The IGBT in the SIMSCAPE environment is of an improved design and has a direct thermal port. The TJ estimation is more accurate and it relies only on the thermal impedance model, so we do not need to compute the power losses as was done in previous studies. This functionality is only accessible in more recent versions of MATLAB (2019-2023). With different motor load torques, the IGBT junction temperature is evaluated, and the effect of the selected heat sink on the value of TJ is evaluated when it is under the effect of natural cooling and air-forced cooling.